2016
DOI: 10.3892/br.2016.784
|View full text |Cite
|
Sign up to set email alerts
|

Animal models for the study of primary and secondary hypertension in humans

Abstract: Hypertension is a significant cause of morbidity and mortality worldwide. It is defined as systolic and diastolic blood pressures (SBP/DBP) >140 and 90 mmHg, respectively. Individuals with an SBP between 120 and 139, or DBP between 80 and 89 mmHg, are said to exhibit pre-hypertension. Hypertension can have primary or secondary causes. Primary or essential hypertension is a multifactorial disease caused by interacting environmental and polygenic factors. Secondary causes are renovascular hypertension, renal dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 111 publications
(92 reference statements)
1
30
1
2
Order By: Relevance
“…It has been found that MrgD expression was higher in the hearts of hypertensive rats compared with those of normotensive rats, and Ang II treatment increased MrgD expression in cardiomyocytes. 13) It has recently been shown that hypertension increased PKA expression in the heart. PKA may be involved in cardiac hypertrophy and LV dysfunction, and alamandine decreased cardiac hypertrophy by inhibiting the PKA pathway.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been found that MrgD expression was higher in the hearts of hypertensive rats compared with those of normotensive rats, and Ang II treatment increased MrgD expression in cardiomyocytes. 13) It has recently been shown that hypertension increased PKA expression in the heart. PKA may be involved in cardiac hypertrophy and LV dysfunction, and alamandine decreased cardiac hypertrophy by inhibiting the PKA pathway.…”
Section: Discussionmentioning
confidence: 99%
“…PKA may be involved in cardiac hypertrophy and LV dysfunction, and alamandine decreased cardiac hypertrophy by inhibiting the PKA pathway. 13) Alamandine has an anti-fibrotic effect in cardiac muscle. 9) It has been shown, a significant decrease in the accumulation of collagen I, collagen III, and fibronectin in isoproterenol-treated rats when they were given alamandine in a dose of 50 µg/kg daily.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic degenerative diseases (hypertension, diabetes, cardiovascular and cancer) have reached epidemic proportions and are considered a serious health problem; therefore, the treatments of these diseases are of clinical importance [32]. In this study, hypertension was induced by unilateral nephrectomy and daily loading with sodium chloride (1%) which resulted in renal hypertension [33,34]. Annona muricata L. (Family: Annonaceae) and Curcuma longa (Family: Curcubitaceae) demonstrated potent antihypertensive properties evidenced by the reversal of the elevated blood pressure, restoration of antioxidants and reduction of oxidants generated in the induced hypertensive state.…”
Section: Discussionmentioning
confidence: 99%